THE MULTIPLE FACETS OF OVERWEIGHT IN CHILD: A SYSTEMATIC REVIEW - Gomes, Maria Juliete Maia (2015)
Introduction: Obesity is a challenging topic in scientific literature; justified by the exponential increasein prevalence in all layers of society. Objective: Identify and review how the published literature discussthe factors that influence the weight gain in children, then suggest possible interventions. Materials andMethods: It was made a systematic review of the most cited publications about the determiners of theoverweight in children, using the databases MEDLINE/Pubmed and SciELO-BR. About the criteria, itwas chosen some articles of free access published on the last 5 years, with researches on both sexes from 0 to12 years old. To reaffirm the quality of the information collected, it was made a checklist/guide to organizeand classify the authors’ ideas. Results: This review consists of 44 articles selected, which were categorizedin three topics: child obesity and healthcare; child obesity and family habits; child obesity and schoolenvironment. Conclusion: The study allowed us to point out the overweight in children’s populations inBrazil and in some developed countries within the period of 5 years. Overweight in children is a real andconstant challenge, therefore, it is noticeable that the educational institution, the healthcare and the familyare essential to the diagnosis, treatment and prevention of child obesity, since it is a complex chronicledisease that requires a mutual effort of the different social spheres aiming to face, by intervention, thisgrave public health problem.